Color Stability and Surface Roughness of Different Composite Resins after Using Different Polishing Systems. - Hisham Z. Abdullah; Bassam K. Amin (Erbil Dental Journal)
Background and objectives: To evaluate and compare the color stability and surface roughness of different composite resins after using different polishing systems and then submitting to accelerating artificial aging (AAA) and staining by black tea.